An innovative tunable bimodal porous PCL/gelatin dressing fabricated by electrospinning and 3D printing for efficient wound healing and scalable production - Ghomi, Erfan Rezvani (2024)
This study presents the development of tunable scaffolds with bimodal porosity comprising poly(ε-caprolactone) (PCL) micro-meshes and PCL/gelatin/ε-polylysine (ε-PL) fibrous layers. Pure PCL scaffolds were prepared using the fused deposition modeling technique featuring grid geometry and interconnected micro-pores, followed by electrospinning to produce PCL/gelatin/ε-PL nanofibrous layers. Field emission scanning electron microscopy was employed to investigate the morphological features of the scaffolds, while the physicomechanical properties were studied using tensile and contact angle tests. Antibacterial performance and skin cell toxicity of the scaffolds were determined by bacterial disc diffusion and cell viability assays, respectively. Morphological analysis showed the presence of micro-to nano-sized pores in the developed scaffolds. The mechanical test results revealed that the prepared scaffolds exhibited Young's modulus values similar to the human skin with higher strain. The nanocomposite scaffolds were cytocompatible and effectively eradicated common bacteria associated with cutaneous wounds. In light of the aforementioned results along with facile fabrication, the tunable PCL/gelatin/ε-PL porous scaffolds hold great promise for applications in skin wound repair.